Clinical and epidemiological characteristics of Guillain Barré Syndrome in three hospitals in Piura, Perú, 2018-2019 - Solano, Fiorela E. (2021)
Guillain-Barré syndrome (GBS) is an acute inflammatory polyradiculoneuropathy with diverse clinical presentations classified as clinical variants, about which little information is available in our region. Objective: To determine the epidemiologic characteristics and the clinic variants of Guillain-Barre Syndrome. Material and Methods: Retrospective cross-sectional study. The clinical records of the suspected cases of GBS in three hospitals in Piura (Northern Perú), between 2018 to 2019, were reviewed. Those with doubtful diagnosis or incomplete histories were excluded. Data were analysed through STATA vs 15.0. Results: Of 123 cases, 61% were male, with an average age of 37, and 36.59% had no previous clinical manifestations. The most frequent comorbidity was high blood pressure. Only 40% of the cases were confirmed. 78% were treated with immunoglobulin. The most frequent variant was AIDP. Conclusions: Guillain-Barre Syndrome occurred more frequently in males and the classical form was the most frequent variant, followed by the regional form. Most cases presented a mild severity level, with 3 as the average degree of disability. Studies on the association between each clinical variant and the clinical characteristics of the disease are recommended.